Augmented Reality Application using Dynamic Location-Based Tracking of Taman Ayun Temple - Buana, Wira; Meily, Sarah Olivia; bin MD. Fudzee, Mohd Farhan (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2021)
Taman Ayun Temple is a world cultural heritage in Bali. Based on observations, information regarding the location at Taman Ayun Temple is still not optimal. This study aims to design an application that displays location information using markerless augmented reality. Markerless AR is a technology that displays virtual objects into the real world using GPS, digital compass, and accelerometer. The application is designed using the Wikitude SDK platform and displays information on location, description, image, distance from the user, and location direction. Data is stored in a database server and managed using the web server. Applications are in Indonesian and English. The testing compares the actual distance with the distance displayed in the application using devices with different OS and RAM. Application speed is less than 1 second depending on RAM and internet speed, while location accuracy depends on smartphone GPS accuracy with a difference of less than 10 meters from the actual distance.